O Ardina de Sapatos Gastos - Bia, Alerto (Fundza, 2022)
Bia, Alerto.– O Ardina de Sapatos Gastos [Livro]. – Maputo : Fundza, 2022. – 82 p.; 21 centímentros.– ISBN: 978-989-8901-58-3
Keywords: Fiction; Short stories